2018
DOI: 10.3390/ijms19092569
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Energy Expenditure and Brown/Beige Thermogenic Activity by Interleukins: New Roles for Old Actors

Abstract: Obesity rates and the burden of metabolic associated diseases are escalating worldwide Energy burning brown and inducible beige adipocytes in human adipose tissues (ATs) have attracted considerable attention due to their therapeutic potential to counteract the deleterious metabolic effects of nutritional overload and overweight. Recent research has highlighted the relevance of resident and recruited ATs immune cell populations and their signalling mediators, cytokines, as modulators of the thermogenic activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 291 publications
(426 reference statements)
0
11
0
1
Order By: Relevance
“…However, there is an increasing amount of evidence that inflammation directly alters the thermogenic activity of brown fat by impairing its energy expenditure mechanism and glucose uptake. Pro-inflammatory cytokines can affect thermogenesis in BAT (104)(105)(106) and also determine the capacity of WAT browning (106,107). It has been clearly demonstrated that infiltrated macrophages and other immune cells in subcutaneous WAT negatively impact the ability of precursor cells to differentiate into thermogenically active beige adipocytes because of pro-inflammatory cytokine secretion and generating an inflammatory microenvironment (108).…”
Section: Impact Of Inflammation and Inflammatory Mediators On Brown Amentioning
confidence: 99%
“…However, there is an increasing amount of evidence that inflammation directly alters the thermogenic activity of brown fat by impairing its energy expenditure mechanism and glucose uptake. Pro-inflammatory cytokines can affect thermogenesis in BAT (104)(105)(106) and also determine the capacity of WAT browning (106,107). It has been clearly demonstrated that infiltrated macrophages and other immune cells in subcutaneous WAT negatively impact the ability of precursor cells to differentiate into thermogenically active beige adipocytes because of pro-inflammatory cytokine secretion and generating an inflammatory microenvironment (108).…”
Section: Impact Of Inflammation and Inflammatory Mediators On Brown Amentioning
confidence: 99%
“…The G allele is more common in lean subjects and subjects with the G174C or G174G genotype have a significantly higher energy expenditure than those with the C174C genotype [43]. IL-6 can influence energy expenditure, improving the stimulation of sympathetic neurons [44].…”
Section: From Health To Disease Statusmentioning
confidence: 99%
“…COX gm RNA and de novo synthesis of an enzyme are induced during the medication of vascular smooth muscle cells with epidermal growth factor 50 or fibroblast and monocytes with early inflammatory inducements like as interleukin-1 51,52 or lipopolysaccharide 53 . Needleman"s and his coworker stated "Clearly, those putative enzyme pools may arise as different gene products, possibly through the expression of different COX genes" in his paper 54 .…”
Section: The Development Of Field and Discovery Of Cox-2mentioning
confidence: 99%